Redefining the Pulvinar Sign in Fabry Disease - Cocozza, S.; Russo, C.; Pisani, A.; Olivo, G.; Riccio, E.; Cervo, A.; Pontillo, G.; Feriozzi, S.; Veroux, M.; Battaglia, Y.; Concolino, D.; Pieruzzi, F.; et al. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: The pulvinar sign refers to exclusive T1WI hyperintensity of the lateral pulvinar. Long considered a common sign of Fabry disease, the pulvinar sign has been reported in many pathologic conditions. The exact incidence of the pulvinar sign has never been tested in representative cohorts of patients with Fabry disease. The aim of this study was to assess the prevalence of the pulvinar sign in Fabry disease by analyzing T1WI in a large Fabry disease cohort, determining whether relaxometry changes could be detected in this region independent of the pulvinar sign positivity.MATERIALS AND METHODS: We retrospectively analyzed brain MR imaging of 133 patients with Fabry disease recruited through specialized care clinics. A subgroup of 26 patients underwent a scan including 2 FLASH sequences for relaxometry that were compared with MRI scans of 34 healthy controls.RESULTS: The pulvinar sign was detected in 4 of 133 patients with Fabry disease (3.0%). These 4 subjects were all adult men (4 of 53, 7.5% of the entire male population) with renal failure and under enzyme replacement therapy. When we tested for discrepancies between Fabry disease and healthy controls in quantitative susceptibility mapping and relaxometry maps, no significant difference emerged for any of the tested variables.CONCLUSIONS: The pulvinar sign has a significantly lower incidence in Fabry disease than previously described. This finding, coupled with a lack of significant differences in quantitative MR imaging, allows hypothesizing that selective involvement of the pulvinar is a rare neuroradiologic sign of Fabry disease.ERTenzyme replacement therapyFDFabry diseaseHChealthy controlsPSpulvinar signqMRIquantitative MRIQSMquantitative susceptibility mappingR1longitudinal relaxation rateR2pure transverse relaxation rate